FACTORS AFFECTING CAPITAL EXPENDITURE IN CITY/REGENCY GOVERNMENTS IN CENTRAL JAVA PROVINCE 2017-2021 WITH ECONOMIC GROWTH AS A MODERATION VARIABLE - Haq, Muhammad Izzul; Syamsuddin, Syamsuddin (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2024)
ABSTRACTIn decentralization, local governments are required to be able to manage their respective fiscal resources, including capital expenditures. high economic growth in a region will ideally increase regional revenues and at the same time increase capital expenditure on the regional government. The purpose of this study is to examine the role of economic growth in moderating the influence of Local Own Revenue (Pendapatan Asli Daerah-PAD), General Allocation Funds (Dana Alokasi Umum-DAU), Special Allocation Funds (Dana Alokasi Khusus-DAK), and Remaining Budget Financing (Sisa Lebih Pembiayaan Anggaran-SILPA) on capital expenditure in Regencies/Cities. in Central Java Province. This research is quantitative using moderated regression analysis (MRA) which was processed with Eviews software version 10. Empirically, in 175 samples consisting of 35 Regency/City Regional Governments in Central Java Province in 2017-2021 it was found that without being moderated economic growth DAU has a positive effect on capital expenditure. Meanwhile PAD, DAK, and SILPA had no positive effect. The existence of economic growth is able to strengthen the influence of PAD and SILPA on Capital Expenditures. However, it was unable to strengthen the influence of the DAU and DAK on capital expenditure.Keywords: Capital Expenditure; Economic Growth; Regional Income ABSTRAKDesentralisasi menuntut pemerintah daerah untuk mampu mengurus sumberdaya fiskalnya masing-masing, termasuk di dalamnya pembelanjaan modal. tingginya pertumbuhan ekonomi suatu daerah idealnya akan meningkatkan penerimaan daerah dan sekaligus meningkatkan pembelanjaan modal. Tujuan dari penelitian ini adalah untuk menguji peran pertumbuhan ekonomi dalam memoderasi pengaruh dari Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU), Dana Alokasi Khusus (DAK), dan Sisa Lebih Pembiayaan Anggaran (SILPA) pada belanja modal pada Kabupaten/Kota di Provinsi Jawa Tengah. Penelitian ini bersifat kuantitatif dengan moderated regression analysis (MRA) yang diolah dengan software Eviews versi 10. Secara Empiris, pada 175 sampel yang terdiri dari 35 Pemerintah Daerah Kabupaten/Kota di Provinsi Jawa Tengah tahun 2017-2021 ditemukan hasil bahwa tanpa dimoderasi pertumbuhan ekonomi DAU berpengaruh positif pada belanja modal. Sementara itu PAD, DAK , dan SILPA tidak berpengaruh positif. Adanya pertumbuhan ekonomi mampu memperkuat pengaruh PAD dan SILPA pada belanja modal. Namun tidak mampu memperkuat pengaruh DAU dan DAK pada belanja modal.Kata Kunci: Belanja Modal; Pendapatan Daerah; Pertumbuhan Ekonomi